Relationship Between the Immunodetection of Alpha-Smooth Muscle Actin and the Aggressiveness of Mammary Papillar Tumors in Female Dog - Mayara Caroline Rosolem; Pamela Rodrigues Reina Moreira; Fábio Nelson Gava; Diego Felipe Alves Batista; Paulo Henrique Leal Bertolo; Maricy Apparício Ferreira; Rosemeri de Oliveira Vasconcelos (Journal of Veterinary Healthcare, 2019)
Papillary carcinoma is a mammary neoplasia of women and female dogs characterized by papillary fibrovascular projections lined by epithelial cells. Evaluation on the biology of these tumors can be done by immunohistochemistry through detection of alpha-smooth muscle actin protein in the papillary myoepithelium, which lacks such a molecule during malignant proliferations. Thus, this study aimed at determining the malignancy degree of papillary mammary tumors of female dogs by immunohistochemistry. Twenty samples of mammary neoplastic tissues collected from female dogs treated in the Veterinary Hospital at FCAV were evaluated by Hematoxylin and Eosin staining (H&E) and tumor cells were immunolabelled with monoclonal antibody to alpha-smooth muscle actin (α-SMA). Five out of 20 cases showed positive immunolabeling greater than 10% of the total immunolabeling. The remaining fourteen cases presented immunostaining lesser than 10% showing decrease or absence of α-SMA labeling in the myoepithelium of the papilla tumors. All those cases in which immunostained cell was over 10% of the neoplasm (5 immunostains of 20 total cases) were classified as benign whereas those below 10% of immunostained in the slid were considered as malignant. Therefore, immunohistochemistry played an essential role in differentiating benign and malignant papillary tumors of bitches as already described for female. Tumor classification by conventional methods, such as H&E staining, can lead to erroneous interpretations on the real biological behavior of the papillary mammary tumor.
Keywords: carcinoma